Theorizing, testing, and concluding for mediation in SCM research: Tutorial and procedural recommendations - Rungtusanatham, M.; Miller, J.W.; Boyer, K.K. (Journal of Operations Management, 2014)
AbstractEmpirical research in Supply Chain Management is increasingly interested in complex models involving mediation effects. We support these endeavors by directing attention to the practices for the theorizing of, the testing for, and the drawing of conclusions about mediation effects. Our paper synthesizes diverse literature in other disciplines to provide an accessible tutorial as to the mathematical foundation of mediation effects and the various methods available to test for these effects. We also provide guidance to SCM scholars in the form of eight recommendations aimed at improving the theorizing of, the testing for, and the drawing of conclusions about mediation effects. Recommendations pertaining to how mediation effects are hypothesized and stated and how to select among methods to test for mediation effects are novel contributions for and beyond the Supply Chain Management discipline.